Intentional coronectomy as an alternative to avoid injuries to the lower alveolar nerve: Clinical case report (Research, Society and Development, 2021)
Introduction: Damage to the Inferior Alveolar Nerve (NAI) is a significant risk factor after removal of an impacted third molar. The absence of cortical bone between the dental root and the mandibular canal, as well as it’s constriction through which the tooth's root passes, are considered signs of high risk of nerve damage. Objective: To report a case of intentional coronaectomy of the lower right third molar, due to intimate contact with the mandibular canal. Patient, female, 19 years old, attended the Dental Specialties Center in Recife, indicated for third molar extraction. Panoramic radiography revealed horizontal impaction of tooth 48, crown contact with second molar roots, and apparent contact with the NAI. Cone beam computed tomography was requested, confirming a close relationship. The chosen approach was intentional coronaectomy and root burial. Conclusion: Literature proves that this technique significantly reduces injury to the inferior alveolar nerve, being an effective and safe alternative to avoid nerve complications.